The Effectiveness of School Principal Leadership Management in Improving Teacher Performance through the BERKARISMA Strategy at Sukorejo IV Public Elementary School - Sa’diyah, Fitriyatus; Harris, Taufiq; Wahyudi , M.Furqon (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the effectiveness of school principal leadership management in improving teacher performance through the BERKARISMA strategy (Quality-Oriented, Creative, Religious, Innovative, Courteous, Independent, and Trustworthy) at Sukorejo IV Public Elementary School, a small school with 76 students and 7 teachers. A qualitative approach with a case study design was used to describe the planning process, supporting and inhibiting factors, and the impact of the strategy. Data were collected through observation, in-depth interviews, and documentation, with triangulation to ensure validity. The results show that the BERKARISMA strategy effectively addressed the limitations of the small school, improved teacher motivation and competencies, and reduced performance gaps (e.g., lesson planning improved from 68% to a more optimal level). Supporting factors included the principal’s role as a role model and team collaboration, while inhibiting factors involved limited resources. The impact was an improvement in the school climate and the quality of learning. This research contributes to the development of leadership models in small schools.